Implementasi Pendidikan Moderasi Beragama Berbasis Internalisasi Nilai-Nilai Islam untuk Membangun Toleransi Sosial dalam Pembelajaran Pendidikan Agama Islam (Studi Kasus Madrasah Aliyah Darul Falah Cermeee Bondowoso) - Kholil Imam; Basriyanto; Luluk Mashluchah; Samsul Arifin; Sumarsi (Kartika: Jurnal Studi Keislaman, 2026)
The implementation of religious moderation education based on the internalization of Islamic values at Madrasah Aliyah Darul Falah Bondowoso aims to strengthen students’ character through Islamic Religious Education (PAI). This study employs a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, display, and verification techniques. The findings show that learning strategies supported by active teacher involvement and pesantren culture effectively instill the values of tawassuth (moderation), tasamuh (tolerance), tawazun (balance), and i‘tidal (justice). Internalization occurs through formal instruction, habituation, social interaction, and teachers’ role modeling. PAI functions as a comprehensive medium for developing moderate and inclusive religious understanding. Its contribution is reflected in increased social tolerance, mutual respect, and the creation of a harmonious, conducive madrasa and pesantren environment that supports balanced character development.